Engineering cocrystals of paliperidone with enhanced solubility and dissolution characteristics - Earle, Radha Rani; Radha, Gadela Venkata (Archives of Pharmacy, 2021)
In the present study, co-crystals (CCs) of Paliperidone (PPD) with coformers like benzoic acid (BA) and P-amino benzoic acid (PABA) were synthesized and characterized to improve the physicochemical properties and dissolution rate. CCs were prepared by the solvent evaporation (SE) technique and were compared with the products formed by neat grinding (NG) and liquid assisted grinding (LAG) in their enhancement of solubility. The formation of CCs was confirmed by the IR spectroscopy, powder X-ray diffraction and thermal analysis methods. The saturation solubility studies indicate that the aqueous solubility of PPD-BA and PPD-PABA CCs was significantly improved to 1.343±0.162mg/ml and 1.964±0.452mg/ml, respectively, in comparison with the PPD solubility of 0.473mg/ml. This increase in solubility is 2.83- and 3.09- fold, respectively. PPD exhibited a poor dissolution of 37.8% in 60min, while the dissolution of the CCs improved tremendously to 96.07% and 89.65% in 60min. CCs of PPD with BA and PABA present a novel approach to overcome the solubility challenges of poorly water-soluble drug PPD.
Keywords: Paliperidone; cocrystal; coformer; solubility; dissolution